Teaching Objectives of the Arabic Conversation Course in Higher Education - Haq, Samsul; Musthofa, Tulus; Baroroh, R. Umi; Muhajir, Muhajir; Shodiq, Muhammad Jafar; Ritonga, Nur'ainun (Scaffolding: Jurnal Pendidikan Islam dan Multikulturalisme, 2026)
This study aims to identify the objectives of teaching the Arabic conversation course and examine the extent to which they align with the Reference Framework for Teaching Arabic to Speakers of Other Languages (Al-Imtāʿ) at Al-Raudhah Al-Hasanah College of Educational Sciences in Medan. This research is a library-based study employing a qualitative, descriptive approach. The primary data consist of the teaching plan for the Conversation course and the Reference Framework for Teaching Arabic to Speakers of Other Languages (Al-Imtāʿ), while the secondary data include relevant books, scholarly articles, and related training materials. Data were collected through documentation and interviews. The data analysis technique used was content analysis, conducted in three stages: data collection, classification, and alignment with the Reference Framework for Teaching Arabic to Speakers of Other Languages (Al-Imtāʿ). The findings indicate that the Conversation course at Al-Raudhah Al-Hasanah College of Educational Sciences in Medan primarily focuses on speaking skills through productive oral expression. Conversation I includes 19 objectives, Conversation II 16 objectives, and Conversation III 16 objectives, which emphasize students’ abilities in narration, expression, explanation, discussion, presentation, and presentation writing. Overall, these objectives align with only 6 of the 24 descriptors of the Reference Framework for Teaching Arabic to Speakers of Other Languages (Al-Imtāʿ). Several objectives align with the Preparatory, Proficiency, and Distinction levels; however, the course objectives were not fully aligned with the framework, as they include writing-related objectives and fail to address 18 of its descriptors.